Identification and Validation of Potential Biomarkers and Their Functions in Acute Kidney Injury - Chen, Jianwen; Chen, Yalei; Olivero, Alberto; Chen, Xiangmei (Frontiers in Genetics, 2020)
Acute kidney injury (AKI) is a global public health concern associated with high morbidity, mortality, and health-care costs, and the therapeutic measures are still limited. This study aims to investigate crucial genes correlated with AKI, and their potential functions, which might contribute to a better understanding of AKI pathogenesis. The high-throughput data GSE52004 and GSE98622 were downloaded from GEO, four GroupSets were extracted and integrated. Differentially expressed genes (DEGs) in the four GroupSets were identified by limma package in R software. The overlapping DEGs among four GroupSets were further analyzed by the VennDiagram package, and their potential functions were analyzed by the GO and KEGG pathway enrichment analyses using the DAVID database. Furthermore, the protein-protein interaction (PPI) network was constructed by STRING, and the functional modules of the PPI network were filtered by MCODE and ClusterOne in Cytoscape. Hub genes of overlapping DEGs were identified by Cyto-Hubba and cytoNCA. The expression of 35 key genes was validated by qRT-PCR. Western Blot and Immunofluorescence were performed to validate an important gene Egr1. A total of 722 overlapping DEGs were differentially expressed in at least three GroupSets. These genes mainly enriched in cell proliferation, fibroblast proliferation. Additionally, 5 significant modules and 21 hub genes, such as Havcr1, Krt20, Sox9, Egr1, Timp1, Serpine1, Edn1 and Apln were screened by analyzing the PPI networks. The 5 significant modules were mainly enriched in Complement and Coagulation cascades and Metabolic pathways, and the top 21 hub genes were mainly enriched in positive regulation of cell proliferation. Through Validation, Krt20 were identified as the top one up-regulated genes with a log2 (fold change) lager than 10 in all these 35 genes, and 21 genes were validated as significantly up-regulated, Egr1 was validated as an up-regulated gene in AKI in both RNA and protein level. In conclusion, by integrated analysis of different high-throughput data and validation by experiment, several crucial genes were identified in AKI, such as Havcr1, Krt20, Sox9, Egr1, Timp1, Serpine1, Edn1, and Apln. These genes were very important in the process of AKI, which could be further utilized to explore novel diagnostic and therapeutic strategies.